THE DOMINANCE OF CREDIT MECHANISMS IN SHARIA TRADING AND ITS IMPLICATIONS FOR THE PRINCIPLE OF TRANSACTIONAL JUSTICE - Cut Dewi Rahma (Mukhtasab: Journal of Economics and Islamic Business, 2026)
The increasing dominance of credit-based mechanisms in contemporary Islamic sales has reshaped the structure and orientation of Sharīʿah-compliant commercial practices. While credit transactions are normatively permissible within Islamic law, their extensive use raises critical questions regarding the realization of transactional justice, which constitutes a fundamental principle of Islamic economics. This study examines the implications of the dominance of credit mechanisms in Islamic sales and evaluates their consistency with the ethical foundations of justice, balance, and mutual benefit embedded in Islamic commercial law. Employing a qualitative normative–conceptual research design, the study adopts the analytical perspectives of fiqh al-muʿāmalāt and Islamic economics. The object of the research is credit-based Islamic sales practices, analyzed through primary data derived from documented transaction practices and contracts, as well as secondary data sourced from classical and contemporary fiqh literature, Sharīʿah fatwas, and Islamic economic scholarship. The findings reveal that credit mechanisms have become the prevailing transactional model, influencing contractual relations, risk allocation, and pricing structures. This dominance tends to generate structural imbalances, particularly through disproportionate risk transfer and rigid obligations imposed on buyers, which may undermine the substantive realization of transactional justice. The study further demonstrates that excessive reliance on credit-oriented models risks marginalizing risk-sharing principles and diluting the moral objectives of Islamic economics. Normatively, the findings suggest that credit mechanisms should function as conditional instruments rather than default transactional frameworks. Practically, the study underscores the need for justice-oriented contractual designs, stronger regulatory oversight, and the promotion of alternative Sharīʿah-compliant models that better align with the objectives of Islamic economics.